1991
DOI: 10.1159/000288423
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategies and Course of Disease of Breast Cancer Patients

Abstract: In a prospective 3-year longitudinal study investigating correlations between coping strategies and course of breast cancer a consecutive series of 107 patients were assessed for biological and psychosocial data. Data analysis indicated no significant correlations between coping strategies and course of cancer. On the other hand, biological parameters such as size of tumor and lymph node stage at time of surgery correlated significantly with the course of disease. It was concluded that the assessed indicators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
3

Year Published

1994
1994
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(17 citation statements)
references
References 9 publications
1
13
0
3
Order By: Relevance
“…Rather, time from the diagnosis to the first recurrence and time to death were significantly associated, in our study, with clinical prognostic variables, especially tumour size and histotype as well as positivity of loco-regional lymph nodes. These findings arc in agreement with studies sug gesting that biological markers, such as tumour volume and involvement of axillary lymph nodes, have a primary and major role in determining the course of breast cancer [33][34][35], Caution is needed in interpreting the results of this study because of a number of important methodological limitations. A first short-coming regards the small num ber of patients in our sample, the different levels of clini cal stage at the psychological assessment and the different treatments received.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Rather, time from the diagnosis to the first recurrence and time to death were significantly associated, in our study, with clinical prognostic variables, especially tumour size and histotype as well as positivity of loco-regional lymph nodes. These findings arc in agreement with studies sug gesting that biological markers, such as tumour volume and involvement of axillary lymph nodes, have a primary and major role in determining the course of breast cancer [33][34][35], Caution is needed in interpreting the results of this study because of a number of important methodological limitations. A first short-coming regards the small num ber of patients in our sample, the different levels of clini cal stage at the psychological assessment and the different treatments received.…”
Section: Discussionsupporting
confidence: 91%
“…dissimu lation, acceptance, diversion), while others (e.g. resigna tion, optimism, emotional release) may change over time and situations [34,59,60], A fourth limitation concerns the extreme complexity of assessing life events in malig nancy and studying the relationship between stressors, coping response and the biological mechanisms underly ing cancer development. Several aspects should be men tioned as potential pitfalls, such as the incomplete or dis torted recall of events (fall-off of event recall) and the con founding effect of the patient's effort to find an explana tion secondary to a life-threatening event such as cancer diagnosis (effort after meaning) [61,62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Good disease outcome in women with breast cancer was reported to be associated with a positive, fighting spirit response (Greer et al, 1979;Pettingale et al, 1985;Greer et al, 1990;Morris et al, 1992;Hislop et al, 1987; Levy and Wise, 1988). By contrast, a minority of studies found no relationship between these coping styles and disease outcome (Cassileth et al, 1985;Jamison et al, 1987;Buddeberg et al, 1991). Patients in the investigations with negative results appear to have more advanced cancer than those in studies which reported positive correlations.…”
Section: Psychological Prognostic Factorsmentioning
confidence: 89%
“…The observed weak associations in this and the previous study (Li et al, 2002) may be because of adaptive lifestyle factors related to stress exposure, or poorer compliance to the medical treatment of the cancer diseases. In addition, disease-related variables or treatment effect, to which we did not have access, may outweigh the influence of psychological stress, if any, on survival (Jamison et al, 1987;Buddeberg et al, 1991;Tross et al, 1996).…”
Section: Discussionmentioning
confidence: 99%